Analisis Tipe Perilaku Konsumen Terhadap Keputusan Membeli Produk Teh di Kota Surakarta - Rina Yuliana; Joko Sutrisno; Tria Rosana Dewi (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Based on the results of the research and analysis that has been carried out, it can be seen first that consumer involvement in the tea purchase decision-making process in the Modern Market of Surakarta is high (31,56 > 24). Second, according to consumers in the Surakarta City Modern Market, the difference between tea brands is not real, meaning that consumers do not see much difference between tea brands. Third, the type of tea consumer behavior in modern markets is dissonance, reducing buying behavior. Usually, consumer behavior is meaningful and goal-oriented. Products are accepted or rejected based on the extent to which both are considered relevant to their needs and lifestyle.